HUBUNGAN JUMLAH LOGAM KROMIUM (Cr) PADA AIR IRIGASI, TANAH SAWAH DAN GABAH DI KAWASAN INDUSTRI DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Sari Mukti Rohmawati; Sutarno Sutarno; Mujiyo Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2017)
Subdistrict Kebakkaramat was the region with the second largest number after sub-district industrial Jaten. Kebakkramat industry in the district is dominated by the textile industry wastewater produced allegedly pollute streams and rivers used by farmers as irrigation water. Waste that pollutes streams and rivers is thought to contain Cr. The use of irrigation water suspected to contain Cr feared to be absorbed by plants and then accumulates in the grain. The purpose of this study was to determine the relationship between the content of Cr in the irrigation water, soil, and paddy rice fields. This research uses descriptive exploratory methods implemented through field surveys and followed by laboratory analysis. Variable observations from this study include Cr. Cr at all observation points, except the control, does not correspond to the irrigation water quality standard, that exceeds a predetermined limit is 0.01 ppm.